Streptomyces as Potential Synthetic Polymer Degraders: A Systematic Review - Maria Fernanda Rodríguez-Fonseca; Jeysson Sánchez-Suárez; Manuel Fernando Valero; Sonia Ruiz-Balaguera; Luis Eduardo Díaz (Bioengineering, 2021)
The inherent resistance of synthetic plastics to degradation has led to an increasing challenge of waste accumulation problem and created a pollution issue that can only be addressed with novel complementary methods such as biodegradation. Since biocontrol is a promising eco-friendly option to address this challenge, the identification of suitable biological agents is a crucial requirement. Among the existing options, organisms of the Streptomyces genus have been reported to biodegrade several complex polymeric macromolecules such as chitin, lignin, and cellulose. Therefore, this systematic review aimed to evaluate the potential of Streptomyces strains for the biodegradation of synthetic plastics. The results showed that although Streptomyces strains are widely distributed in different ecosystems in nature, few studies have explored their capacity as degraders of synthetic polymers. Moreover, most of the research in this field has focused on Streptomyces strains with promising biotransforming potential against polyethylene-like polymers. Our findings suggest that this field of study is still in the early stages of development. Moreover, considering the diverse ecological niches associated with Streptomyces, these actinobacteria could serve as complementary agents for plastic waste management and thereby enhance carbon cycle dynamics.